Design and Implementation of Digital Education Resources Blockchain-Based Authentication System - Tri Wahyuningsih; Gunawan; Fitra Putri Oganda; Mey Anggraeni (IAIC Bangun Bangsa, 2021)
With the approaching of the digital age, digital education resources bring convenience to folks as a result of they're liable to duplicate and spread, however there are some disadvantages in on-line education service transactions. The safety problems with digital education resources and also the development of smuggled distribution seriously harm the rights and interests of the house owners of digital education resources. supported this, during this paper, we have a tendency to planned a blockchain-based digital education resources authentication system that uses the decentralized, tamper-resistant options of blockchain technology to store the digital education resources info within the style of a secret text. Within the system, there is no have to be compelled to need the participation of any third-party institution. The system planned during this study can greatly defend the rights and interests of the owner of digital education resources.